Are Language Teaching Methods Really Dead as Some TESOL Gurus Have Proclaimed? - Jesus Alirio Bastidas (Profile: Issues in Teachers' Professional Development)
Up to the last two decades of the 20th century, the era of methods prevailed as a key component, especially in the field of teaching English as a second language. Nevertheless, by the end of the century, many TESOL authorities were questioning the usefulness and scope of methods. Consequently, the idea was declared dead and the postmethod condition emerged. In this reflection article, it is argued that the nature and scope of a method in the teaching field cannot die for a series of reasons. It is concluded that what can be proclaimed is the death of a unique, universal method, but not the death of methods per se, since this is an essential component of any teaching process.